GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 763988283 species occurrences available in GBIF matching the query: TaxonKey: Animalia. The dataset includes 763988283 records from 15205 constituent datasets: 69 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Vireonidae. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 15 records from Nannofossil abundance of Hole 24-232. 44 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 1189 records from UWIZM Molluscs. 7 records from The inaequalis species-group (Hymenoptera, Chrysididae, Chrysis) in China, with description of a new species. 78 records from Nannofossil abundance of Hole 36-329. 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 382 records from orthopteracollections-nhmj-ioj. 824 records from Bird specimens of Saitama Museum of Natural History. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 9 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 1 records from A new species of Lepidocyrtus (Collembola, Entomobryidae) from the Börzsöny Mountains, Hungary. 6 records from A new species of the genus Euhemicera (Tenebrionidae: Cnodalonini) from South East Asia, with an updated catalogue of all known species. 20 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 7 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 13 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 55 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 42 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 7 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 173 records from UWIZM Anoles. 10 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 1 records from Nothrus pulverulentus. 63 records from Pollen analysis of sediment profile TR0 from Truennensee. 2379 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 20 records from Condamine Alliance. 7 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 55 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 425 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 48 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 8 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 27 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 21 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 43 records from Faunal assemblage of sediment core TR149-31. 599 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 165061 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 4 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 169 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 3 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 1006 records from Colecção Entomológica IIA. 6701 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 17155 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 5 records from Nannofossil abundance of Hole 10-91. 6943 records from DMNS Egg Collection (Arctos). 14922 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini). 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 221 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 5782 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 1 records from Orthoptera - SMF. 1 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 287870 records from Florida Keys Reef Visual Census 2014. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 10 records from New species of Diatrichalus (Coleoptera: Lycidae) from New Guinea and the Moluccas. 672 records from Colección de Entomología - Curculionidae. 6 records from Taxonomy of the European Pied Flycatcher Ficedula hypoleuca (Aves: Muscicapidae). 30 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 13 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 22180 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 53859 records from Records from the NIWA AllSeaBio marine biology database. 3 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 6237 records from Plecoptera. 52 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 9 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 3 records from Benthic hydroids (Cnidaria: Hydrozoa) from off George V Coast (East Antarctica). 14 records from New species, new records and updated subgeneric key of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from India. 14 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 5 records from Redescription and phylogenetic analysis of the type species of the giant pill-millipede genus Sphaeropoeus Brandt, 1833 (Diplopoda, Sphaerotheriida, Zephroniidae). 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 61948 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 67 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 39 records from Nassau Mountain Expeditions 2005/2006/2010/2014. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 38 records from Neogene palynomorpha from site 81-552. 120 records from BIRDRACE The early birds. 1289 records from RECORD Orthoptera Data. 2 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 3 records from A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica. 115 records from Antarctic Pycnogonids II. 10 records from Oberservation of birds at station PS14/143 along 49° West. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1935 records from ISM Ichthyology Collection. 6979 records from Upper Silesian Museum, Bird Observations. 1628 records from Données naturalistes de Quentin ROME. 1 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 124 records from SEWBReC Springtails and allies (South East Wales). 5 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 7 records from Nannofossil abundance of Hole 9-79. 1 records from Formiciden aus dem Naturhistorischen Museum in Hamburg. II. Teil. Neueingaenge seit 1900 (PP). 60 records from Artenvielfalt auf dem Schulgelände. 10389 records from National Museum of Natural Science. 41 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 22 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 17 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1557 records from Hermatypic Corals of Western Australia. 322 records from Collections ichtyologiques et herpétologiques (BOUM). 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 6192 records from NE Scotland fish records 1800-2010. 2 records from A new Panolis Hübner, [1821] species from Vietnam (Lepidoptera, Noctuidae, Orthosiini). 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 23 records from Pollen profile ADR353. 270 records from bmhs_weatherheadshell_collection. 6 records from Sächsische Schweiz (Pfaffenstein). 11955 records from Données ONEMA BDMAP 2014. 578 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 27 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 6 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 285321 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 220 records from Living Cirripedia. 11 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 38 records from Roter Berg Werdau (Leubnitz). 36 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 15 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3755 records from Données naturalistes de Charlotte PICARD. 8 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 5 records from Ostracoda abundance of Hole 44-390. 7 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhingidae. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 29 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Mercedes (Unterkofler, octubre 1999). 31 records from Nannofossil abundance of Hole 60-458. 47 records from Waldstück Bremerhagen LK Bio Kl. 12. 1 records from A new vertebrate for Europe: the discovery of a range-restricted relict viper in the western Italian Alps. 7 records from Phase-contrast synchrotron microtomography reveals the internal morphology of a new fossil species of the Corticaria-sylvicola - group (Coleoptera: Latridiidae). 39 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 581 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 4 records from Range table from benthic foraminifers in ODP Hole 146-889A. 45797 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 141 records from Bannwald Burghauser Forst. 21162 records from SEWBReC Bees, Wasps and Ants (South East Wales). 1 records from Araboplia lorisi new genus and species of Rutelinae from Saudi Arabia (Coleoptera, Scarabaeidae), with comments on the subtribe Popilliina. 1 records from Redescription of the thread-legged assassin bug Ploiaria anak (Hemiptera: Heteroptera: Reduviidae: Emesinae) from India, with notes on its biology. 2780 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 25 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 877 records from COA Bird Collection (Arctos). 77 records from Sorensen distance for herbivores. 5 records from First record of the genus Doliopteryx Hesse, 1956 (Diptera: Mythicomyiidae: Glabellulinae) from Iran, with description of two new species. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 40 records from Resolving the taxonomy and nomenclature of Metochus abbreviatus (Hemiptera: Heteroptera: Rhyparochromidae). 10 records from A revision of and keys to the genera of the Mantispinae of the Oriental and Palearctic regions (Neuroptera: Mantispidae). 30 records from Artenvielfalt des "Grünen Klassenzimmers". 2 records from Neue Milbenarten aus Kärnten. 53406 records from Entomology Collection at the Natural History Museum of Utah. 1 records from A PArtial Skeleton of the Tyrannosaurid Dinosaur Aublysodon from the Upper Cretaceous of New Mexico. 114 records from BIRDRACE LiLaLau. 94857 records from Fish specimens of Kagoshima University Museum. 4185 records from Diptera Collection of Museum and Institute of Zoology PAS. 4048 records from UTEP Invertebrates (Arctos). 26 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 23 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 2 records from A new species of Pegylis Erichson, 1847 (Coleoptera: Scarabaeidae: Melolonthinae: Pegylini) from Ethiopia. 14 records from Relative abundance of coccosphere-units at site GIK23414. 20 records from New records of the larval forms Cerataspis monstrosa and Amphionides reynaudii (Crustacea: Decapoda) from the western tropical Atlantic. 23643 records from CNIN/Abejas de México/Apoidea. 2272 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 11 records from Ostracod species in Oligocene sediments of core CRP-3. 2 records from Nannofossil abundance of Hole 10-93. 2194 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 12 records from Art´n Vielfalt im Kinderwald. 76 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 287 records from UF Environmental Archaeology Tick Island Zooarchaeological Data. 16 records from Benthic macrofauna abundance of sediment core 13077-093. 21 records from Riedkanal Bötzingen. 7 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 2 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 1030501 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 22 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 4 records from Loricifera - SMF. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 44 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 480819 records from KTP Ring Data. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 196 records from Collection des mammifères d'Auvergne. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 16469 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1109 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 48 records from Morphologische Daten von Natrix. 26 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 689 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 9 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 95 records from BIRDRACE accipiter hardcore birding. 89 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 9 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 4749 records from CNAC/Coleccion Nacional de Acaros. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 63 records from Nannofossil abundance of Hole 4-31. 628 records from hauterivian_echinoids_of_the_paris_basin. 14 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 218 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 149 records from BioAcoustica: Wildlife Sounds Database. 7 records from TransForest vegetation data. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 101 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 203 records from Schanzenanlage Bergham. 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 75 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 234 records from Données Phesulma borbonica du Parc national de La Réunion - COBE03. 122 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 444 records from Marsabit Ecosystem Inventory Surveys 2014. 3 records from Dactylogyrids (Monogenea) parasitic on marine fish from Peru including the description of a new species of Haliotrema Johnston & Tiegs, 1922 and two new species of Parancylodiscoides Caballero & C. & Bravo-Hollis, 1961. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 118 records from Nannofossil abundance of Hole 37-334. 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 20 records from Schulgelände SGD/Viersen. 42 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 1 records from Zur Kenntnis der Lithobiiden. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 11 records from Nannofossil abundance of Hole 84-570. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 10 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 2 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 892 records from (UTC) University of Tennessee Mammals Collection. 21773 records from Birds Specimens. 57 records from Schulgelände Kranich-Gymnasium (Salzgitter). 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 33 records from Fliegenhaupt Marksuhl. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 18811 records from DMNS Mammal Collection (Arctos). 110 records from Occurrence of mammalia relicts at site Rejtek 1. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 881 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 82 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 230 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 11 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 1744 records from BenthosChukchiFN762_1976_Falk5. 38 records from Nannofossil abundance of Hole 15-154A. 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 119 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 1870 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 66 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 10170 records from Données de la collection d'ichtyologie du MNHN (GICIM). 104 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 8516 records from Données naturalistes de Bruno OGER. 13 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 65903 records from Norwegian Lepidoptera working group. 26 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 71 records from Occurrence of mammalia relicts at site Pestera Bursucilor. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 49 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 61 records from Knechtweide (Kohlfurth). 18 records from Benthic macrofauna abundance of sediment core 12930-073. 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 89 records from Meniscus Midges (Dixidae) of Ireland. 73 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 170 records from Alien Species in Poland - Animals. 23 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 80 records from Natura 2000 PnrL. 1378 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 973 records from Zambian Bat Collections Worldwide. 8 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 1196 records from Entomological collection of the National Museum. 143 records from BIRDRACE Punkbirder Helgoland. 1 records from Miriapodi di alcune grotte della Campania. 554 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 52 records from Nannofossil abundance of Hole 4-29. 2497 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 28 records from Naturpark Kottenforst-Ville 15.6.09. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 11 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 10 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 127 records from FFH-Gebiet Klosterwasser/Burkau. 16 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 256 records from Données naturalistes de Hubert GUIMIER. 1717 records from Collection rousset -1947-2013. 1857 records from Données naturalistes de Hervé BOUYON. 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 254 records from Thistle Heads and Ermerged Insects. 177 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 1 records from An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado. 365 records from Colección Herpetológica de la Patagonia. 1 records from Description of a new species of genus Trachischium with a redescription of Trachischium fuscum (Serpentes: Colubridae: Natricinae). 4 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 1 records from Earthworm species in various land use systems in the Campos Gerais region of Lapa, Paraná, Brazil. 25 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanterriidae).. 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 3527 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 27 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3078 records from Insectes Hyménoptères Scollidés de France. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 3 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4313 records from Weddell Sea macrozoobenthos EASIZ I. 916 records from IOW Natural History & Archaeological Society Marine Records. 17 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 5559 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 14 records from Occurrence of mammalia relicts at site Climauti II. 81 records from Waldi-Weiher. 18 records from Phase 2 Lowland Grassland Survey of Wales. 163 records from Invasive Non-Native Species, Outer Hebrides. 296 records from Gewann Krampf (Heilbronn). 110441 records from Naturalis Biodiversity Center (NL) - Crustacea. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 389 records from Amphibian and Reptilian (KIEE-AR). 44 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 12147 records from Danish Ants (Formicidae). 17 records from Benthic macrofauna abundance of sediment core 13201-002. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 1029 records from Circumpolar Seabird Monitoring Plan. 16 records from Pollen profile from Muscotah Marsh B. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 48 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 60 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 2733 records from Palaeobiology collection, FAU Erlangen. 25093 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 1285805 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 413272 records from DATAVES. 8 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 56 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1 records from Hemichordata collection of National Museum of Nature and Science. 27 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 2 records from ATCC Bacteria Collection Catalog. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1659 records from The Broward College Insect Collection. 23 records from Abundance of benthos infauna at station GIK23042-2. 79 records from Culture Collection of Algae. 23824 records from Collection Vermes - ZMB. 130 records from BIRDRACE - The famous Grouse feat. The James. 789678 records from Western Australian Museum provider for OZCAM. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 43 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 424 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 742 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 2 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 31 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 21 records from Waldstück am Schullandheim Bad Bederkesa. 170 records from Coarse fraction analysis and texture of biogenous sands from Josephine Seamount surface samples (Table 2). 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 1513 records from M. Gollop Collection. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 53166 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Données naturalistes d'Olivier DELZONS. 18 records from Schulgarten der Gesamtschule Am Heidberg. 19 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 2 records from Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic. 53 records from Leopard and Weddell seal program 1999/2002. 3268 records from Données naturalistes de Ségolène FAUSTEN. 3 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 103 records from Invertebrate collections. 4 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 17114 records from Collection of Coleoptera. 39 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 64 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 9 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 3269 records from Benthos Chirnov Basin 1986 and 2002. 821086 records from Queensland Museum provider for OZCAM. 27 records from Coccoliths in sediment core GIK23065-3. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 251 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 6 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 701 records from Données naturalistes d'Arnaud LE NEVÉ. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 1 records from Analyses of the recent components of sediment core PS1219-1. 717 records from Redland City Council Citizen Science Portal. 44759 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 17 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 180 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 78 records from Steinbruch Mainz-Weisenau, 3. Jahr. 1536 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 32 records from Pollen profile V and Ausfluss at Krumbach, Germany. 622 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 197435 records from UMMZ Herpetology Collection. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 2789 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 36 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 1 records from Berlese's Primitive Oribatid Mites. 23 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 5 records from Society Islands beach bum black flies (Diptera: Simuliidae). 174 records from BIRDRACE Bon(n)apartemöwen. 74 records from Nannofossil abundance of Hole 75-532. 62 records from Données de Mammifères marins en Polynésie française issues du South Pacific Whale Research Consortium. 1 records from A new species of Andinobates (Anura: Dendrobatidae) from the Urabá region of Colombia. 2726 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 12 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 28 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 515 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 81329 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 307 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 2 records from Macrocyrtus imomzodai Barševskis, 2016, a new synonym of Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 (Coleoptera: Curculionidae: Entiminae). 35 records from Reptiles Specimens of Akita Prefectural Museum. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 6 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 340 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 339 records from UWIZM Snakes. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 97 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 8 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 16 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 218 records from Heinersdorfer Sumpfwiese. 133650 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 291402 records from ARABEL - Arachnologia Belgica. 95 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 23562 records from Arctic Species Trend Index (ASTI) : Marine. 1 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 7 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 1 records from A new species of the genus Megophrys (Anura: Megophryidae) from Yunnan Province, China. 21 records from Nannofossil abundance of Hole 85-573. 10 records from Catalogue of Ampulicidae, Crabronidae and Sphecidae of Iran (Hymenoptera, Apoidea). 33333 records from Wolli Creek Preservation Society Bird Survey. 348 records from Antarctic pycnogonids. 1 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 1 records from Seven new species of Night Frogs (Anura, Nyctibatrachidae) from the Western Ghats Biodiversity Hotspot of India, with remarkably high diversity of diminutive forms. 62776 records from MLZ Bird Collection (Arctos). 3 records from Redescription of Honduriella maxima Denmark & Evans (Acari: Mesostigmata: Phytoseiidae), description of a new species of Honduriella Denmark & Evans from the Amazonian Forest, and a modified characterisation of the genus. 31 records from Naturschutzgebiet Müchelholz (Mücheln). 22 records from Microzooplankton abundance and biomass at station TT043_27-1. 1 records from Brachiopods Specimens of Akita Prefectural Museum. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 31 records from Wiese am Waldrand (Gurtweil). 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 4 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 6 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 3 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 6 records from Two new species of Nemouridae (Plecoptera) from Vietnam. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 43 records from Renaturierung Werse (Innenbereich Beckum). 351 records from UWYMV Herpetology Collection (Arctos). 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 292 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 6672 records from Midden-Limburg Fish Ponds Survey. 6 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 11454 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 175 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 8 records from Herbarium Senckenbergianum (FR) - Fungi. 2000 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 6478 records from National System of Protected Areas in Poland - Animals. 20191 records from Seabirds in Norway - Estimated population sizes. 11 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 8 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 22 records from Plant specimens of Bihoro Museum. 55 records from Occurrence of mammalia relicts at site Rusenschloß. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 82 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 4193 records from Leicestershire and Rutland Aculeate Records. 1 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 113 records from South Lanarkshire peatland records 2013. 15 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 10110 records from Suivi Temporel des Libellules (STELI). 1032 records from Étude entomologique des forêts publiques de Martinique, pour l'ONF. 944 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 1653 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 2 records from Two new species of the genus Daptonema Cobb, 1920 (Nematoda: Xyalidae) found in an intertidal seagrass bed on the coast of the Andaman Sea, Thailand, with reference to the taxonomic status of the genus Trichotheristus Wieser, 1956. 100 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 3 records from Abundance of radiolaria at station UT99-23-2. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 132 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 52 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 859 records from Floral visits on plants, InsectScale 2008. 2091 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 688 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 3 records from F. L. de Castelnau’s Norman River fishes housed in the Macleay Museum, University of Sydney. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 6 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1 records from One new species of Amphinemura and description of the female of A. ancistroidea Li & Yang (Plecoptera: Nemouridae) from Guangxi Zhuang Autonomous Region of southern China. 3 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 35 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 6 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 43 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 9 records from Review of Pennella Oken, 1816 (Copepoda: Pennellidae) with a description of Pennella benzi sp. nov., a parasite of Escolar, Lepidocybium flavobrunneum (Pisces) in the northwest Atlantic Ocean. 22 records from Ostracoda abundance of Hole 24-238. 8 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 15 records from Meiofauna abundance in sediment core 54301-010. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 678 records from Collection Hydrozoa - ZSM München. 2 records from Redescription of the Amazonian tiny tree toad Amazophrynella minuta (Melin, 1941) (Anura: Bufonidae) from its type locality. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 5 records from Distribution of nanoplankton at trap WR2. 79 records from Birdrace-Bielefinken-Bielefeld. 13624 records from Ecosphère_2017_12_18. 49 records from Müritz-Nationalpark. 125 records from Range table from ostracoda in ODP Hole 143-866B. 11 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 14 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 30 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 4654 records from Colección Limnológica Universidad de Antioquia. 3 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 92 records from Wald am Schloss Wittgenstein Bad Laasphe. 659 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 168538 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 3529 records from A dataset from bottom trawl survey around Taiwan. 58 records from Isle of Wight non-native invasive species. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 3 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 90 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 696 records from Données naturalistes de François BRETON. 11 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 2 records from A new slipper lobster of the genus Petrarctus Holthuis, 2002 (Crustacea, Decapoda, Scyllaridae) from Southwest coast of India. 2 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 21 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 26728 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 12 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 149 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 5 records from Die Bachspezies 2008/2009. 83 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 30008 records from Lepidoptera specimen database of Japan. 308173 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 2499 records from Leicestershire and Rutland Reptile Records to 2011. 45140 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 5 records from Streuobstwiese. 194767 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 19 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 90 records from Steinbruch Mainz-Weisenau, 2. Jahr. 1 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 9057 records from NE Scotland other invertebrate records 1800-2010. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 2174 records from ConDidact Citizen Science Surveys - Snails 2006. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 26 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 34 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 28 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 43 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 125 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 89 records from Deponie Klausdorf. 30 records from Schulgelände (Wetter). 34 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 16 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 6 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 15 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 2387 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 2 records from Foraminifera abundance of Hole 74-526A. 14387 records from Enquête Lucane. 432 records from Erlengraben/Lipp-Tal (Östringen). 71 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1984 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 39 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 6 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 392 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 4 records from Overview of Niphargidae (Crustacea: Amphipoda) in Belgium: distribution, taxonomic notes and conservation issues. 5698 records from EDIT - ATBI in Gemer area (Slovakia). 14 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 43 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 24 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 22137 records from Global compendium of Aedes albopictus occurrence. 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2548 records from BioGIS - Reptiles - HUJ collections. 40 records from Teich Berlin Wuhlheide. 5 records from An overview of the genus Plesionika Bate, 1888 (Decapoda, Caridea, Pandalidae) in Asian waters. 3 records from Nannofossil abundance of Hole 27-259. 1 records from Analyses of the recent components of sediment core PS1222-1. 22042 records from UTEP Vertebrates. 24 records from Coccoliths in sediment core PS1535-8. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 17 records from AKG-Gelände (Bensheim). 15 records from Flora Atlas N.T.. 1 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 5449 records from Fishes in the Argentine Sea from 1967 to the present time. 1 records from Occurrence of mammalia relicts at site Raagelund. 54 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 3 records from Paracercion ambiguum sp. nov. from Lang Son, Vietnam (Zygoptera: Coenagrionidae). 5 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 4926 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 85 records from Ostracoda abundance of Hole 48-403. 79 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 232 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 8 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 32 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1589 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 16128 records from Colección Ictiológica del Instituto Alexander von Humboldt. 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 139 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 159 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 550 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 10 records from Ostracoda abundance of Hole 32-306. 33 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 6 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 283 records from Antarctic Amphipoda. 49 records from Lebensraum Gesamtschule (Langerwehe). 20 records from Foraminifera abundance of Hole 64-481. 61 records from Nannofossil abundance of Hole 29-281. 3796 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 59680 records from Butterflies of Ireland. 17 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 905 records from Coléoptères Silphidés du département du Loiret. 9 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 68269 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27264 records from Formidabel; Belgian Ants Database. 2557 records from Fish (NHMK-PI). 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 2 records from The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 493 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 42 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 4 records from Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification. 87535 records from MDFRC macroinvertebrate survey. 54 records from Données naturalistes de Pauline BALDUCCI. 17 records from Amtsrain Apolda-Zottelstedt. 15 records from PROJET DE CONSTRUCTION D’UNE ROUTE DE TRANSPORT DES MINERAIS DE BAUXITE DE GAC: EIES, inventaire des amphibiens (CESP2016-022). 135 records from DIBA-Parc del Montnegre i el Corredor. 22 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 4764 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 9 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 35 records from Planktic foraminifera abundance of Hole 40-362A. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 83 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 8 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 21456 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 3 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 7 records from Grundwasserlebensraum im Englischen Garten (München). 18 records from The socially parasitic ant genus Strongylognathus Mayr in North Africa (Insecta: Hymenoptera: Formicidae).. 213 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 32 records from Nannofossil abundance of Hole 31-299. 10 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 115 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 206 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 2952 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 31663 records from MCP - Coleção de Abelhas. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 19 records from Erhard Sopp. 2711844 records from First Bird Atlas. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 1153 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 22 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 382 records from Reptilia ZMK. 102 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 7 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 42 records from Planktic foraminifera abundance of Hole 15-149. 142 records from Pollen profile RAC20, Lake Racou, France. 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 280 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 31 records from Lepidurus arcticus survey Northeast Greenland 2013. 90 records from Natura 2000 Vallée de la Seille. 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 10898 records from Inventario de Hymenóptera; parasítica en México. 48 records from VSN-Wiese. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 23 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 1 records from A new scale insect of the extinct family Weitschatidae (Insecta: Hemiptera: Coccomorpha) from mid-Cretaceous Burmese amber. 21541 records from MfN - Fossil Fish Collection. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 814 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 190 records from Relative abundance of ostracods in sediment core Sv09. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 750 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 181977 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 32 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 48 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 76 records from BIRDRACE Nachtigallen. 6 records from Nannofossil abundance of Hole 24-233A. 3006 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 217 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 104 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 4579 records from Estación Biológica de Doñana - CSIC, Anfibios. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 1 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 267243 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 6 records from Cave-dwelling crabs of the genus Karstarma from lava tubes of the volcano ‘ Piton de la Fournaise’, in Réunion Island, with description of a new species and redescription of Karstarma jacksoni (Balss, 1934) from Christmas Island (Decapoda, Brachyura, Sesarmidae). 408 records from Birds Specimens of Akita Prefectural Museum. 10172 records from UAM Fish Collection (Arctos). 1163 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 5 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 2 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 70 records from Isotope tracer experiment: meiofauna counts. 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 26511 records from MSUM Ichthyology and Herpetology Collections. 557 records from Corn bunting breeding distribution in Scotland. 14 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 7122 records from Whale catches in the Southern Ocean. 25 records from Two new species of the gobiid fish Trimma from the coral reefs of the western Pacific Ocean (Pisces; Perciformes; Gobioidei).. 16 records from Benthic macrofauna abundance of sediment core 13200-008. 2324 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 71 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 33 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 1 records from Nannofossil abundance of Hole 94-611E. 8 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 1 records from Centre de Ressources Biologiques de l'Institut Pasteur. 17961 records from River Biologists' Database (EPA). 66 records from Selztal bei Friesenheim. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 801 records from Great Eastern Ranges - Slopes to Summit. 18 records from Microzooplankton abundance and biomass at station TT045_19-3. 17077 records from UCM Mammal Collection (Arctos). 126 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 97827 records from Tiroler Landesmuseum Ferdinandeum. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 6 records from Skeletal Adaptations of Ornitholestes, Struthiomimus, Tyrannosaurus. 9 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 43 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 68 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 54 records from Pollen profile from a swamp at Seelohe, Fichtelgebirge, Germany. 2 records from Natural History Museum, Vienna - Herbarium W. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 9206 records from Weddell Seal census, Vestfold Hills, Antarctica. 78 records from Mammals (GNHM-MM). 7 records from Quadrige. 8851 records from Odonata records from RSPB Reserves 1970-2009. 1038 records from Données supplémentaires Atlas des Mammifères marins. 2697 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 18 records from Anfibios presentes en el Cerro Jánano. 35 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1591312 records from NBIS Records to December 2016. 306 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 187 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 39 records from Dorfrand Mauderode. 411 records from SuLaMa reptile survey I 2012. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 61 records from Shrews of Poland. 1 records from Nannofossil abundance of Hole 2-11. 10 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 178 records from Données naturalistes de Pascal Dupont. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 40 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 28062 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 22 records from Aglaotilla, a new genus of Australian Mutillidae (Hymenoptera) with metallic coloration. 54 records from Faunal assemblage of sediment core GS7603-13. 318 records from Bird specimens of Bihoro Museum. 1 records from Discovery of a new species of Dryocosmus Giraud, 1859 (Hymenoptera: Cynipidae: Cynipini) on Castanopsis tibetana from China. 147 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 3 records from Nannofossil abundance of Hole 6-48B. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 181089 records from Marine benthic dataset (version 1) commissioned by UKOOA. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 1689 records from HerpMapper. 985 records from Freshwater Fishes of Bulgaria. 60 records from Nannofossil abundance of Hole 4-25. 29876 records from European Moth Nights. 2 records from Genetic evidence supports Sylvilagus mansuetus (Lagomorpha: Leporidae) as a subspecies of S. bachmani. 5406 records from Colección de Anfibios. 1820 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 11135 records from NBMB Herps. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 434 records from Aves de Caño Cristales, La Macarena, Meta. 4 records from MfN - Micropaleontology. 5 records from USU-UTC Specimen Database. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 5979 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 116 records from Umgebung der Gesamtschule Hamburg-Winterhude. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 1584 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 296 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 525 records from BUND - Dassower See (Lübeck/Dassow). 25 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 86 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 69 records from Birds and plant species near Petushki town (Vladimir region). 1242 records from Revues diverses et littérature grise.. 70 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 114 records from (Table 4) Thecosomata in ODP Hole 134-831A. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 2 records from Sächsische Schweiz (Wehlener Gebiet). 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 59 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 5 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 113 records from Appendicularia abundance of station M9_A near the Great Meteor Bank, Northeast Atlantic (Table 1). 568 records from Expedición Providencia I - INVEMAR. 962 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 1 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 16 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6042 records from Arthur Chapman Observations. 307 records from Cuxhavener Küstenheiden. 5 records from Two new species of genus Lasiosina Becker from China (Diptera, Chloropidae). 211055 records from UMMZ Birds Collection. 285 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 7 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 2391 records from UWYMV Bird Collection (Arctos). 1458655 records from Hatikka Observation Database. 1 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 55 records from Foraminifera abundance of Hole 61-462. 128214 records from inatura - Erlebnis Naturschau Dornbirn. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 19 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 364 records from Coleoptera identified from the Borax Works, Norman Road site, Bexley, London. 3 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 2018 records from Birds (NHMK-BI). 933 records from Collection Graptolithina fossil SMF. 956 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 11 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 1273663 records from PlutoF platform observations. 7 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 11 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 171 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 6 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 9 records from Three new species of the millipede genus Hyleoglomeris Verhoeff, 1910 from the Aegean region of Greece (Diplopoda, Glomerida, Glomeridae). 1 records from Two new species of Tenuipalpus Donnadieu, 1875 (Acari: Trombidiformes: Tenuipalpidae) from Iran. 63 records from Marine gastropod distribution from patagonian shallow waters. 54 records from "Ahrschleife bei Altenahr". 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 6 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 472970 records from South Australian Museum Australia provider for OZCAM. 25 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 1 records from Two new species of obligatory termitophilous rove beetles from Brazil (Coleoptera: Staphylinidae: Termitomorpha Wasmann). 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 7834 records from DASSH Data Archive Centre volunteer survey data. 1 records from New fossil genus of Silvanidae (Insecta: Coleoptera) from Baltic amber (Tertiary, Eocene). 10 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 47 records from Unter hellen Zinnen und finsteren Grotten. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 7 records from Range table from planktonic foraminifers in ODP Hole 177-1088C. 119 records from BIRDRACE Immerwiederhopf. 309 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 8 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 5 records from A description of three new species of the genus Alienia Fibiger, 2011 from Southeast Asia (Lepidoptera, Erebidae, Hypenodinae: Micronoctuini). 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 2366 records from Modernisation des ZNIEFF du PnrL. 38 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 1 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 7 records from Collection Malakologie - SMNG. 20 records from Occurrence of mammalia relicts at site Niederlehme. 86 records from UWIZM Cnidarians. 4 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 9810 records from Royal British Columbia Museum Entomology Collection. 27 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 324 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 7 records from The first elateroid beetles (Coleoptera: Polyphaga: Elateroidea) from the Upper Jurassic of Australia. 280 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 24 records from MVZ Herp Observations (Arctos). 29 records from Occurrence of mammalia relicts at site Großes Schulerloch. 157 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 29 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 5 records from Cladocera from the Upper Xingu River Basin with the description of a new genus of the Chydoridae (Crustacea: Branchiopoda: Anomopoda). 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 3005 records from Colección Entomológica CDMB. 1 records from A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo. 4 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 253 records from Données naturalistes d'Olivier LAURENT. 2867 records from Restauración y conservación de Isla Guadalupe. 16933 records from Lepidoptera (Specimens NRM). 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 5428 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 993 records from ROC RSPB Farmland Species Survey Dataset. 205 records from Wild boar sightings held by Andy Riches. 6 records from Wuhle - Brücke / B1. 182049 records from Florida Keys Reef Visual Census 1999. 62 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 94 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 3 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 27810 records from Collection of saproxylic and xylobiont Beetles. 10 records from Occurrence of mammalia relicts at site Meiendorf. 111 records from BIRDRACE Die Wendehälse. 88 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 22586 records from Tachinid Recording Scheme - GB and Ireland records. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 83 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 8332 records from Scotland Otter Survey Database. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Pandionidae. 4617 records from Données de type contact de Guadeloupe. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 6 records from Canadian Museum of Nature Palynology Collection. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 1602 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 1284 records from Données naturalistes de Thomas LORICH. 89 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 38 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 2 records from New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India. 2 records from Osteology and relationships of Libanopycnodus wenzi gen. et sp. nov. and Sigmapycnodus giganteus gen. et sp. nov. (Pycnodontiformes) from the Late Cretaceous of Lebanon. 10 records from DSMZ Bacteria. 47 records from Galls on Beech Trees in Hainich, 2008. 2039 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 237813 records from CAS Entomology (ENT). 4104 records from Naturalis Biodiversity Center (NL) - Pisces. 158987 records from Carnet B Lorraine. 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 32 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 3 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 1). 31788 records from Observatoire de la Biodiversité des Jardins (OBJ). 277999 records from Seasearch Marine Surveys in England. 47 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 1 records from Arthropoden aus südostalpinen Höhlen.. 2 records from Nannofossil abundance of Hole 10-94. 118 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 1 records from Ctenophora ZMK. 9 records from Studies in Mexican Grasshoppers: A new species of Pedies Saussure (Acrididae: Melanoplinae) with comments on the unusual blue coloration on the abdomens of females and live specimen images for three other congenerics. 38 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 19 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 7 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 14009 records from Collection Trichoptera - SMF. 5 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 94 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 21 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 82 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 72 records from Range table from nannofossils in ODP Hole 164-994C. 11 records from Nannofossil abundance of Hole 1-3. 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 255 records from Occurrence of mammalia relicts at site Raj Cave. 12 records from Nannofossil abundance of Hole 6-55. 2 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 24 records from Pollen analysis of sediment core GeoB6518-1. 9 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 80 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 96068 records from Arizona State University Hasbrouck Insect Collection. 64 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 3618 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_AMPHIBIA. 63364 records from CCAMLR historic KRILL. 430 records from Collection Strepsiptera SMF. 94 records from Quarrendorfer Landschaftsschutzgebiet. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 168 records from Registros de quirópteros de tres localidades del caribe colombiano. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3587 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 228 records from Chironomid remains in the sediment sequence of Site PG1212. 34 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 6 records from Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan. 1 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 29 records from BMHS Crustacean Collection. 30 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 119 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 440 records from Antarctic and Subantarctic Asteroid zoogeography. 5 records from New species and records of Omaliini from East Asia (Coleoptera: Staphylinidae: Omaliinae). 24 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 286 records from Coastal and Marine Species Database. 39 records from Nannofossil abundance of Hole 67-499. 275 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 152215 records from Tasmanian Museum and Art Gallery provider for OZCAM. 40119 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 968 records from TTRS Mammals. 54 records from Weidegebiete in der Selzrenaturierung. 212 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 148 records from Occurrence of mammalia relicts at site Veternica. 744 records from Ostracoda in sediment core PS51/159-10. 66 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 3 records from Lampetra soljani, a new brook lamprey from the southern Adriatic Sea basin (Petromyzontiformes: Petromyzontidae). 9 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 6 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 834295 records from Liste des espèces de la faune sauvage (Amphibiens, Mammifères hors Chiroptères, Oiseaux, Orthoptères, Reptiles & Rhopalocères) observées selon le maillage communal français de la base de données naturalistes Faune-France .. 35 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 6 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 1 records from Description of females of Chilarboreus Ruta, 2011 (Coleoptera: Scirtidae: Scirtinae). 401 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 6083 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 1004 records from HBRG P.F. Entwistle Notebooks Dataset. 242 records from UTEP Fish (Arctos). 95 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 7 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 2 records from Mormolyce matejmiciaki sp. nov. (Coleoptera: Carabidae: Lebiinae) from Borneo. 99389 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 43 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 58 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 31 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 6 records from New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam). 90 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 49 records from Faunal assemblage of sediment core TR149-32. 121 records from Nannofossil abundance of Hole 15-149. 4 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 2 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 82 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1913 records from Registros Primates Neotropicales Convocatoria APC. 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 41 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 19 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 5 records from Pollen record of profile 3TZ2. 15691 records from Mollusques dulcicoles de France - Jacques MOUTHON. 606 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 1 records from Hoplophora ardua. 43 records from Bases de datos de plantas, insectos, reptiles, anfibios, aves y mamíferos del “Arroyo la Junta, Una joya de biodiversidad en la Reserva de la Biosfera Sierra La Laguna”. 621 records from BID-Malawi-Geometridae-Biodiversity-Data. 94 records from A new species of the Liolaemus alticolor - bibronii group (Iguania: Liolaemidae) from East-central Argentina. 190 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 31 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 81596 records from Collection Aves (bird skins) SMF. 1 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 14 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 4054 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 18 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 17 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 34 records from Morphological examination and phylogenetic analysis clarify the taxonomic status of Cuban Longior Travassos & Kloss, 1958 (Nematoda: Thelastomatoidea: Hystrignathidae). 1 records from Nymph inadvertently described as new species for a fourth time? On the identity of Euscelimena hardi (Tetrigidae: Scelimeninae) with general remarks on the identification of pygmy grasshopper nymphs. 373 records from Otter survey of Ireland 2004 & 2005. 4 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 31 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 67 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 84 records from BIRDRACE Vogelscheuchen. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 112 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 81 records from Birdrace-Die_Ornithomaten-Herford. 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 292 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 6183 records from SANBI: DNA Banking(1987-2011). 21 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 20266 records from The national database for marine data (MADS). 38109 records from Naturalis Biodiversity Center (NL) - Mammalia. 3 records from Nannofossil abundance of Hole 9-82. 16 records from Microzooplankton abundance and biomass at station TT043_11-1. 8 records from Foraminifera abundance of Hole 57-440A. 63 records from Nannofossil abundance of Hole 74-525A. 2082 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 7 records from Taxonomy of deep-water tetillid sponges (Porifera, Demospongiae, Spirophorina) from Brazil, with description of three new species and new characters. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 16 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 101 records from BIRDRACE Enger am Spektiv. 3715 records from Ghent university - Zoology Museum - Nematod Collection. 17 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 2 records from ParaindOPaMPHantus bruneiensis gen. nov. et sp. nov., as the first representative of the subfamily Pamphantinae from South East Asia (Hemiptera: Heteroptera: Geocoridae: Pamphantinae: Indopamphantini). 4 records from Taxonomic changes in Salyavatinae (Heteroptera: Reduviidae), with an updated generic key. 18 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 2884 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 5 records from Warnowufer Groß Klein. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 4 records from Stadtrandlandschaft Apolda-Nord. 12 records from A new species of Podocinum (Acari: Podocinidae) from Brazil, and supplementary descriptions of three species of this genus. 45 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 11 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 23238 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 36 records from Nannofossil abundance of Hole 49-410. 216 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 2 records from A new species of Globicornis Latreille (Coleoptera: Dermestidae) from Baltic amber, with a key to fossil species. 16 records from Hazel Dormouse in Ireland. 4 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 1 records from A new African Apiocera species (Apioceridae, Diptera). 164878 records from CAS Invertebrate Zoology (IZ). 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 844 records from Colección Aracnológica del IADIZA-CCT CONICET Mendoza: IADIZA-CAI. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 98 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 17 records from Planktic foraminifera abundance of Hole 14-142. 39329 records from Insects, Outer Hebrides. 830 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 118 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 17 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 9 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 1 records from Occurrence of mammalia relicts at site Ballybetagh. 25446 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 505 records from National Frog Survey of Ireland 2010/2011. 5 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 5361 records from Colección Ornitológica de la Universidad del Valle. 111 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 7 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 2780 records from Marine Turtles. 750 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 207 records from Données de Mammifères marins. Mission AGOA de 2012 à 2014. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 3 records from A new subfamily, Styracurinae, and new genus, Styracura, for Himantura schmardae (Werner, 1904) and Himantura pacifica (Beebe & Tee-Van, 1941) (Chondrichthyes: Myliobatiformes). 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 6 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 19 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 50 records from Revision of the genus Shairella Chûjô, 1962 (Coleoptera: Chrysomelidae: Galerucinae) from Taiwan, with descriptions of five new species. 7 records from Deep-sea ascidians from Papua New Guinea. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 25 records from Nannofossil abundance of Hole 67-499B. 77 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 607156 records from NatureServe Network Species Occurrence Data. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 41676 records from Tagged Seal Location Data from SOGLOBEC. 11 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 333 records from Données naturalistes de Renaud PUISSAUVE. 310556 records from Dry Tortugas Reef Visual Census 2010. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 207 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 4 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 173 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 1709 records from The Gibson spider collection. 34 records from Naturgrundstück (Eutin). 68 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 8 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 95 records from Truppenübungsplatz Panzerkaserne Böblingen. 651 records from Réseaux écologiques/Trame verte et bleue. 36 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 3 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 381 records from Coelenterata (Cnidaria and Ctenophora) collection of National Museum of Nature and Science. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 66164 records from Florida Keys Reef Visual Census 1996. 3 records from Zoology in the Middle East. 4 records from Pollichia Pilzherbar. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 159 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 16 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 58 records from Neogene palynomorpha from site 93-603, part 2. 14 records from Review of the leafhopper genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 24387 records from Données de Luc BARBARO. 611 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 189 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 5448 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6757 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 829 records from If_Ecologie_Conseil_2017_12_18. 5 records from On the types species of the New World dung beetle genus Canthidium Erichson, 1847 (Coleoptera: Scarabaeidae: Scarabaeinae), with an annotated checklist of species. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 238 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 36 records from Nannofossil abundance of Hole 49-408. 1 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 20 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 1 records from Analyses of the recent components of sediment core PS1011-1. 368 records from Biological Recording in Scotland - Bumblebee Survey. 1 records from Allan Herbarium (CHR). 253763 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from Pinguisoperla, a new fossil genus of Perlidae (Insecta: Plecoptera) from mid-Cretaceous Burmese amber. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 103 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 48 records from Zoo Frankfurt. 11470 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 128 records from BIRDRACE Oostfreesland Bird-Lopers. 1 records from Description of a new species of Acrostichus Rahm 1928 (Nematoda: Diplogastridae) from India with a note on its position and relationship with the congeners. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 157 records from Canada_BasinMegabenthos2002. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 105326 records from Database of invertebrates collected in Mongolia. 26 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1081 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 10075 records from Nematoda of Costa Rica (INBio). 32912 records from Insect specimen database of Atsugi City Museum. 75 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 62 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 9 records from Two new species of Elacatinus (Teleostei: Gobiidae) from the Mexican coast of the Gulf of Mexico.. 34 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 1112 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 356 records from Morphologische Daten von Puffinus creatopus. 9076 records from WTSWW Data: All Taxa (West Wales). 614 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 6 records from Pollen record of profile 3TZ. 433 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 82 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 238 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 322193 records from Florida Keys Reef Visual Census 2010. 38839 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 27 records from Pollen data of trap CB4. 15 records from A new species of Aculus mite (Acari: Eriophyidae), a potential biocontrol agent for Australian swamp stonecrop, Crassula helmsii (Crassulaceae). 14 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 153 records from annex1. 1048 records from Sutton Hoo species data held by The National Trust. 1 records from Nothrus bicarinatus. 1 records from Nannofossil abundance of Hole 66-493A. 10 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 58 records from Draubiotop Lavamünd. 5 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 25 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 549 records from Netzfluegler_Raw1. 64 records from "Schwarzwassertal" bei Pobershau. 164 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 1 records from Occurrence of mammalia relicts at site Ejstrup. 8328 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 28382 records from Plan de vertebrados de la Patagonia. 25 records from Fleas (Siphonaptera) of Turkey: species composition, geographical distribution and host associations. 92 records from Birdrace_TerraCamper-Münster. 6 records from Revised status of Oridryas Meyrick, 1938: new synonyms of Ypsolopha Latreille, 1796, and Ypsolopha parenthesella (Linnaeus, 1761) (Yponomeutoidea: Ypsolophidae). 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 8 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 30 records from AlgaTerra. 5 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Occurrence of mammalia relicts at site Igstadt I. 134559 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 65 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 553 records from Danielsberg (Mölltal, Kärnten). 6775 records from MfN - Fossil vertebrates III. 1 records from Nannofossil abundance of Hole 39-353A. 16988 records from LPO_PACA_2017_12_18. 90 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 5 records from Studies on the Zoarcidae (Teleostei: Perciformes) of the southern hemisphere. IX. A new species of Pachycara from the southwestern Atlantic.. 1 records from Oklahoma Vascular Plants Database Provider. 60 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 11 records from Borkhart. 8601 records from HSU Vertebrate Museum Mammals Collection. 153 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 740 records from Targeting a portion of central European spider diversity for permanent preservation. 3464 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 3 records from Nannofossil abundance of Hole 9-80. 6 records from Two new species of Miltochrista from India (Lepidoptera, Erebidae, Arctiinae). 4 records from Liste des pays par taxon spécimen TOGO. 46 records from Nannofossil abundance of Hole 3-15. 2064 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 18 records from Foraminifera abundance of Hole 57-440B. 95 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 238 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 99 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 9 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 6 records from The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species. 239 records from Rutilans. 18 records from Camiguin, Philippines Fauna. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 516 records from UTEP Insects (Arctos). 2682 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 36 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 25 records from Occurrence of mammalia relicts at site Bivak Cave. 308 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 2 records from Données naturalistes de DURON Cyril. 31638 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 99 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 2 records from Omophorus (Sinomophorus) wallaCei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae). 28141 records from Collection Pisces SMF. 4 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 7 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 13 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 98 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 8486 records from Insect (ENHM-IN). 32 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 348 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 19 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 346 records from Packer Collection /Madagascar. 18 records from Rediscovery and redescription of Laelaps lignicola G. & R. Canestrini, a remarkable myrmecophilous mite of the genus Cosmolaelaps Berlese (Acari: Mesostigmata: Laelapidae) from Italy. 2223 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 26 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 17807 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 18 records from Predatory Dinosaurs of the World. 230 records from Nivå Bay species list, Zealand, Denmark. 7 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 3294 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 100 records from Nannofossil abundance of Hole 64-476. 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 189 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 2188 records from Données naturalistes de Matthias COLIN. 53 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 76262 records from Colección de Entomología del Instituto Alexander von Humboldt. 158 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 57 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 129544 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 1861 records from Cowan Tetrapod Collection - Herpetology. 1 records from On the Chilopoda from Turkey. 910 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 12448 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 678 records from Upper Silesian Museum, Bird Collection. 2 records from Phytoplankton abundance at station CD46_0705C#4. 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 3 records from New synonymies in the plant bug family Miridae (Hemiptera: Heteroptera) from Northern China. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 4172 records from CASES2003_2004. 3 records from Nouvelles fourmis de Madagascar.. 13 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 2 records from A review of the genus Syrianarpia Leraut (Crambidae: Scopariinae) with description of S. elburzalis sp. n. from Iran. 1120 records from Shellfish (MNHM-MS). 11 records from Hemmerder Schelk (Unna). 36510 records from Fife Nature Records Centre combined dataset. 34 records from An der Ohm, (Wettsaasen). 292 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 13 records from Nannofossil abundance of Hole 73-521A. 31 records from Skull anatomy and phylogenetic assessment of a large specimen of Ecteniniidae (Eucynodontia: Probainognathia) from the Upper Triassic of southern Brazil. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 19 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 8 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 148 records from Abundance of birds in the Lena Delta Region. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 8 records from Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae. 29 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 39 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 6 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 345 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 2 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 103 records from Mammals (UWEP-MM). 84981 records from NINA Vanndata fisk. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 510 records from Inventaires des cygnes du département de l'Eure. 6 records from New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean. 10 records from Landwehrbach. 9921 records from CSIRO, fish surveys by the Soela, 1980s. 27 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 4 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 32 records from Artenvielfalt in der Kinderakademie im RFZ. 33 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 63 records from Microfossil abundance of Hole 16-158. 42 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 30 records from Nannofossil abundance of Hole 78-543. 25 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 53062 records from British Antarctic Survey Argos satellite tracking data. 1365 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 1162 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 1 records from Abcoronalis protrusus, a new paraboloponine genus and species (Hemiptera: Cicadellidae: Deltocephalinae: Drabescini) from Borneo. 2 records from A new genus of Trichogrammatidae (Hymenoptera: Chalcidoidea) from India. 1 records from Zetes pallidulus. 1 records from A new jellynose, Ateleopus edentatus, from the western Pacific Ocean (Teleostei: Ateleopodiformes: Ateleopodidae). 72 records from A review of Synegiodes Swinhoe, 1892 (Lepidoptera: Geometridae), with description of two new species. 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 600 records from Growth and age across range extension region of Centrostephanus rodgersii in eastern Tasmania and morphometric comparison of urchins inhabiting kelp versus barrens habitats, Australia (2004-2005). 1 records from A new record of Potamanthellus caenoides Ulmer 1939 (Ephemeroptera: Neoephemereidae) from the southern Western Ghats of India. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 14 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 8462 records from University Of Pretoria: Lacewing Database Project (1911-2015). 20 records from Freiheitsring (Frechen). 13 records from Nannofossil abundance of Hole 66-490. 4400 records from USAC Mammals Collection. 5 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 5 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 63 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 2 records from Erythrodiplax ana sp. nov. (Odonata: Libellulidae) from Brazilian palm swamps. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 6992 records from Stone-curlew Annual Surveys. 29646 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 20 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 218 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 3399 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 287 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 5 records from On the identity of Sternosternus grouvellei Guillebeau, 1894 (Coleoptera: Hydrophilidae, Phalacridae). 1 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 16 records from Taxonomic review of the genus Wasmannia.. 29 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 2350 records from Données naturalistes de Bernard Lalanne-Cassou. 12761 records from Données naturalistes de Franck NOEL. 363 records from PSUZC-Reptile Collection. 82 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 93 records from Nannofossil abundance of Hole 82-558A. 1470 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 70 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 323 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 2 records from Tamdamaeus staryi gen. nov., sp. nov. (Acari, Oribatida, Damaeidae) from Vietnam, with remarks on certain unusual diagnostic features. 3 records from A new species of Oncopeltus Stål, 1868 (Heteroptera: Lygaeidae) in the nominate subgenus from Ecuador. 3327 records from BioGIS - Mammals - SPNI. 59 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 25919 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 91840 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 1 records from Diatom abundance of Hole 60-460. 917519 records from SEWBReC Birds (South East Wales). 1 records from First columbellid species (Gastropoda: Buccinoidea) from deep-sea hydrothermal vents, discovered in Okinawa Trough, Japan. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 75 records from Luderbusch. 1308 records from Heigham Holmes species data held by The National Trust. 39903 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 8 records from Teich im Wald zwischen Böblingen und Schönaich. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 2495 records from Collections data on ecology of bottom animal of the Southern ocean. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 36 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 5611 records from Collection Echinodermata SMF. 18326 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 76484 records from MfN - Fossil vertebrates IV. 12 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 6303 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 52 records from Occurrence of mammalia relicts at site Zigeunerfels. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 5 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 132045 records from Amphibiens et Reptiles de France (Enquête 2). 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 26918 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 9304 records from Echinoderm collection of National Museum of Nature and Science. 82 records from Wirbach-Taubental (Bad Blankenburg). 109176 records from Herps Specimens. 54 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 1450 records from Données naturalistes d'Alain BERLY. 30535 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 6 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 180886 records from LSUMZ Birds Collection. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 57 records from Chromidotilapia melaniae and C. nana, two new cichlid species (Perciformes, Cichlidae) from Gabon, Central Africa.. 13 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 221 records from (Table 6) Ostracod assemblages of sediment core 9409. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 1698 records from Red-throated diver national surveys in Scotland - raw data. 28 records from Description of two new Calicnemia from Vietnam and central Laos with notes on their congeners in Vietnam (Odonata: Platycnemididae). 220 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 10698 records from Yoann_BLANCHON_2017_12_18. 14833 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 13 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 8 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 3 records from MSB Mammal Observations (Arctos). 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 4 records from Two new Afrotropical genera of Scatopsidae (Diptera). 5046 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 61296 records from Données "faune" hors insectes pour le SINP île de France. 10 records from Données naturalistes de Sophie COHEN. 129 records from Occurrence of mammalia relicts at site Burghöhle Dietfurt. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 6 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 41 records from New and poorly known Meligethes Stephens from China, with bionomical data on some species (Coleoptera: Nitidulidae: Meligethinae). 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 10 records from Nannofossil abundance of Hole 17-167. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1 records from Arthropoden aus südostalpinen Höhlen.. 2644 records from Database of Australasian Vertebrate Occurrences. 289 records from bmhs_butterfly_collection. 124 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 29 records from Abundance of benthos infauna at station POS128/2_284. 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 15 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 171 records from checklist-of-birds-of-zomba-mountain. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 110866 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 90 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 27988 records from Bird records for Argyll for the years 2002 and 2003. 65 records from MfN - Fossil plants (Paleophytic). 3853 records from Données naturalistes de Loïc SALAUN. 2 records from SWECO. 5247 records from Ibaraki Nature Museum, Fish collection. 24 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 3 records from A new genus and new species of Potamidea (Crustacea: Decapoda: Brachyura: Potamoidae), the first stygomorphic cave crab known from China and East Asia. 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 6 records from New records of two endemic troglobitic and threatened arachnids (Amblypygi and Opiliones) from limestone caves of Minas Gerais state, southeast Brazil. 1939 records from East Ayrshire Species Database. 91 records from CNIN/Tipos Homoptera. 270 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 328 records from Otter (Lutra lutra), Outer Hebrides. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 30 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 81712 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 3 records from The male of the orb-weaving spider Plebs mitratus (Simon, 1895) and a redescription of the female (Araneae, Araneidae). 18 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 195 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 3 records from Tobrilus saprophagus sp. n. and Epitobrilus interstitialis sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 29638 records from Collection Crustacea - ZMB. 66 records from Range table from ostracoda in ODP Hole 151-910D. 874 records from The Living Murray Fish data. 742 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 18 records from Peckoltia cavatica, a new loricariid catfish from Guyana and a redescription of P. braueri (Eigenmann 1912) (Siluriformes).. 30 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 6 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 1 records from Nannofossil abundance of Hole 25-249. 25887 records from Long-term Bird Census in Cigu 2004-2017. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of the puparium of Hermetia pulchra (Diptera: Stratiomyidae) from Brazil. 13 records from Nannofossil abundance of Hole 24-233. 1464 records from CNIN/Tipos Coleoptera. 4 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 246 records from BARTH-Environnement_2017_12_18. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 81 records from A checklist of Leiodidae (Coleoptera: Staphylinoidea) of Iran. 3 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 154 records from Dermaptera in the icipe collection. 12 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 33 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 25 records from Additional new species of the genus Obolopteryx Cohn et al. 2014 (Ensifera: Tettigoniidae) from Northeastern Mexico. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 50 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 10 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 3 records from First record of Gauguin's blunt-nose lizardfish, Trachinocephalus gauguini Polanco, Acero & Betancur 2016 (Teleostei: Synodontidae) outside the Marquesas Archipelago. 32 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 20 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 75 records from Ridge to Reef Marine Monitoring of Fanga'uta Lagoon, Tonga, October 2017. 47 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 640 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 836 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 35 records from Naturschutzgebiet Lochbusch-Königswiesen. 16 records from Two new deep-water species of the genus Thorogobius (Teleostei: Gobiidae) from the upper continental slope of the Eastern Central Atlantic. 2 records from Bolletino del Museo Civico di Storia Naturale di Verona, Botanica Zoologica [2000-]. 65 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 277 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 12 records from A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini). 272 records from BIRDRACE Niederlausitz-Team. 7814 records from Odonata de Veracruz. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 478 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 49 records from Schulgarten Huttenheim (Philippsburg/Baden). 2 records from A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species. 59 records from Planktic foraminifera abundance of Hole 18-173. 881 records from Moluscos Marinhos de Augusto Nobre. 4 records from Occurrence of Anafroptilum Kluge 2012 (Ephemeroptera: Baetidae) in Oriental Region. 159 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 21 records from Plant (JNHM-PL). 513 records from Poissons et Crustacés d'eau douce de la Martinique. 1778 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 6250 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 157 records from Loup 2009 présence régulière communale (réseau Loup-Lynx ONCFS). 1001 records from LACM Invertebrate Paleontology. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 10 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 59 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 99 records from Composition of the coccolith flora in sediment core GeoB1710-3. 635 records from CG04_2017_12_18. 377 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 11 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 127 records from Collection Ephemeroptera - SMF. 22 records from Microzooplankton abundance and biomass at station TT045_15-2. 10437 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 1016 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 437 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 16 records from Occurrence of mammalia relicts at site Pestera lui Climente I. 300 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 102450 records from Denver Museum of Nature & Science - Entomology. 1 records from Ubristes rex sp. n., a new microdontine hoverfly from northern Brazil (Diptera: Syrphidae: Microdontinae). 38 records from Nannofossil abundance of Hole 47-398. 9 records from The millipede family Paradoxosomatidae in the Philippines, with a description of Eustrongylosoma penevi sp.n., and notes on Anoplodesmus anthracinus Pocock, 1895, recorded in Malaysia and Sri Lanka for the first time (Diplopoda, Polydesmida). 626 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 34615 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 35 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 41 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 1 records from Capture of Primary Biodiversity Data for West African Plants. 74 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 2 records from Arthropoden aus südostalpinen Höhlen.. 9000 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 61 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 14 records from Taxonomy of Euschizomerus Chaudoir 1850 (Coleoptera: Carabidae: Panagaeinae) from India with a new species and new synonym. 2 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 19 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 588 records from MVZ Hildebrand Collection (Arctos). 44 records from (Table 17) Nannoplankton distribution in sediment core ANS3-T4. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 10180 records from Spider (NSMK-SP). 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 3 records from Nannofossil abundance of Hole 58-442B. 6 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 23 records from Taxonomy and ecology of a new species of Corynura (Hymenoptera: Halictidae: Augochlorini) from Chile and Argentina. 10 records from First record of the spider genus Wolongia Zhu, Kim & Song, 1997 from India with the description of a new species (Araneae, Tetragnathidae). 56125 records from National Biodiversity Data Bank. Observation records, 1900-2014. 1503 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 433 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 4 records from VFD-H: Heidenrod: Pferdeweide Mürth. 12418 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1 records from Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili). 426 records from Données du Centre de la mer de Biarritz. 56 records from Données 2015 de l'Observatoire de la Biodiversité des Forêts. 12217 records from California State University, Long Beach Mammals. 18 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 70 records from Revisions of Australian ground-hunting spiders. V. A new lycosoid genus from eastern Australia (Araneae: Tengellidae). 5 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 5071 records from Données de mammifères enregistrées dans BazNat - Lot 2. 1357 records from Ostracoda in sediment core PS51/154-11. 1 records from A new moss salamander, genus Nototriton (Caudata: Plethodontidae), from the Cordillera de Talamanca, in the Costa Rica-Panama border region. 6 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 3387 records from Données avifaune de Guadeloupe. 28 records from Planktic foraminifera abundance of Hole 23-219. 22434 records from UMNH Reptiles and Amphibians Collection (Arctos). 7 records from Gymnothorax pseudotile sp. nov. (Muraenidae: Muraeninae) from Bay of Bengal India. 1 records from Heterochronic evolution explains novel body shape in a Triassic coelacanth from Switzerland. 1824 records from CNAN/Scorpiones. 98 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 1831 records from Fossil (WSHN-FO). 4 records from A new species of the genus Pseudotrachystola Breuning (Coleoptera: Cerambycidae: Lamiinae) from China. 4 records from Two new genera and species of the leafhopper tribe Idiocerini (Hemiptera: Cicadellidae) and redescription of the type species of Paraidioscopus. 32 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 198-1207A. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 7 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 133902 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 114 records from BIRDRACE Di-Bi-Di-Birder. 13 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 156 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 109 records from A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae). 2238 records from Cnidaria MZS. 378 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 26 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 6923 records from Museu de Ciències Naturals de Barcelona: MCNB-Pal. 133 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 13 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 14 records from Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae). 28 records from Occurrence of mammalia relicts at site Geyerloch. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 302 records from Malawi-Cicindelidae-Biodiversity-Data. 18058 records from Fish Collection of Yokosuka City Museum. 4 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 22 records from The fishery ground near Alexandria. XVI. Cumacea, stomatopoda, leptostraca by Adolf Steuer (1938).Notes and Memoirs No 26.. 4507 records from ARC-PPRI: National Collection of Insects: Coleoptera Collection (1879-2012). 38 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 44921 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 65 records from Landschaftspflegehof (Berlin). 9 records from Bachpatenschaft Beeke. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 18224 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 354 records from SPC CoFish Invertebrates Observations Niue 2005. 693 records from Gemeinde Sursee. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 50 records from Nannofossil abundance of Hole 67-496. 5224 records from Insect specimens of Omogo Mountain Museum. 852 records from OMMAG_Suivi_Dauphins_Les_Saintes. 101 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 19 records from Occurrence of mammalia relicts at site Nazeing. 91 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 194 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 41 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 493 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 220 records from Inventario de Mamíferos Mámbita. 2 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 59461 records from Canadian Museum of Nature Mammal Collection. 1 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 6 records from Pollen and spore abundance of Hole 42-381. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 231066 records from Estonian Nature Observations Database. 12 records from Naturpark Sternberger Seenland. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 589 records from Birds (NMNO-BI). 147674 records from Biodiversitätsdatenbank des Landes Salzburg. 27 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 17713 records from NCSM Mammals Collection. 3 records from Nannofossil abundance of Hole 52-418. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 100 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 28 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 4417 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 459 records from DMNS Parasite Collection (Arctos). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 4 records from A new brachypterous species of Phoberus MacLeay (Coleoptera: Trogidae) and status changes of species in the East African P. nigrociliatus group. 9 records from Nannofossil abundance of Hole 20-200. 48 records from Pollen profile Märchenwald B, Harz, Germany. 46 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 31917 records from Mollusca of Costa Rica (INBio). 6 records from Mammalia (JNHM-MM). 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 4 records from Two new species of Prionomastix Mayr (Hymenoptera: Encyrtidae) with a key to Indian species. 2 records from Phylloicus mirabilis (Trichoptera: Calamoceratidae), a new species from Rio de Janeiro state, southeastern Brazil. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 2 records from Notes on two rare conger eel species (Anguilliformes: Congridae) found in Taiwanese waters. 6288 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 10 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 379 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 3 records from Foraminifera abundance of Hole 45-396. 755529 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 10 records from Ice Amphipods Canada Basin. 5 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 14 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 189 records from (Figure 4) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-549A. 1125 records from Données naturalistes de Stéphane ORIO. 5327 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 664 records from Collection Echinodermata - ZMB. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 7 records from Revision of Thaumatocranaus Roewer, 1932, with description of two new species (Opiliones: Laniatores: Gonyleptoidea). 97 records from WildesMoor bei Schwabstedt. 443 records from Inventario herpetofaunístico del noroeste de Hidalgo. 3668 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 4 records from New fossil taxa of Ischalia Pascoe (Coleoptera: Ischaliidae) from Eocene Baltic amber. 8054 records from ZooplanktonBeaufortSeaNOGAP2. 12 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 48 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part II. 34 records from Freshwater Gastropods of Taveuni. 234 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 2 records from The genus Neoheegeria with a new species from Iran exhibiting wing-dimorphism (Thysanoptera: Phlaeothripidae). 4 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 11 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 448 records from Harpactus Shuckard. 2500 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 16 records from Microzooplankton abundance and biomass at station TT045_26-3. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 67 records from (Table 1) Distribution of Pleistocene calcareous nannofossils in ODP Hole105-646A. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 41 records from List of Snail species in Vava'u. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 3 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1 records from A new species of Rock Gecko of the genus Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from Belitung Island, Indonesia. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 25 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 2 records from New ichneumonids (Hymenoptera, Ichneumonidae) from the Eocene Tadushi Formation, Russian Far East. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 105 records from Fish Fauna of Berlin. 1 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 12 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 8865 records from SMNS Palaeontological collection - Invertebrates (Jurassic and Cretaceous). 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 37 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 36 records from Phytoplankton abundance in surface water during cruise CD61. 6 records from "Schlechteberg" Ebersbach/Sa.. 17 records from Contribution to the knowledge of Cloeodes Traver 1938 (Ephemeroptera, Baetidae). 9519 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 2004 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 91 records from Phytoseiid mites (Acari: Phytoseiidae) associated with tropical ornamental plants, with a checklist and a key to the species of Bahia, Brazil. 101 records from Collection des données de biodiversité marine de Polynésie française. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 303 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 2 records from Scirtothrips genus-group in Iran with an unusual new species of Scirtothrips (Thysanoptera: Thripidae). 2 records from Anophtalmic and epigean? Description of an intriguing new species of Hyalella (Amphipoda, Hyalellidae) from Brazil. 3 records from (Table 2) Eocene benthic foraminiferal community of DSDP Holes 95-613 and 11-108. 1756594 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 4 records from Nannofossil abundance of Hole 1-3. 266 records from MfN - Fossil invertebrates IIa. 1170 records from Département_du_Var_2017_12_18. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 26 records from Schulgarten Waldorfschule Hassfurt. 13 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 48 records from Wildlife Observations Bardon Hill 31.5.09. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 193 records from Loup 2009 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 121 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 8 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 4054 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 12932 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 7 records from Partial redescription of pontoniine shrimps Cuapetes nilandensis (Borradaile, 1915) and Cuapetes seychellensis (Borradaile, 1915) (Decapoda: Palaemonidae: Pontoniinae) with remarks on taxonomic status of Cuapetes Clark, 1919 and Kemponia Bruce, 2004. 280 records from Macrofauna, entomofauna y vegetación vascular de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 2 records from Nannofossil abundance of Hole 3-22. 18 records from Review of the Paratydeidae (Acari: Prostigmata), with description of three new species. 9 records from New taxa of pygmephoroid mites (Acari: Pygmephoroidea: Pygmephoridae, Neopygmephoridae) phoretic on Enoplotrupes sharpi (Coleoptera: Geotrupidae) from Thailand. 1594 records from Musée Vert ornithology collection. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 1103 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 896 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 87 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 20 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 27012 records from RHS lily beetle (Lilioceris lilii) monitoring. 3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 5406 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 272 records from Lacewings (Neuroptera) of Ireland. 91356 records from 臺灣兩棲類資源調查與教育宣導推廣計畫 Resources survey and education advocacy to promote for Taiwan amphibian resources. 159 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 89 records from A review of the genus Potemnemus Thomson, 1864 (Coleoptera: Cerambycidae) with description of a new species from Papua New Guinea. 25 records from New lineages of Lebinthini from Australia (Orthoptera: Gryllidae: Eneopterinae). 315 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 61798 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 134 records from BIRDRACE Griffin Wood Warblers. 3 records from Kystfuruskoger 2015. 2 records from Porifera ZMK. 94 records from Collection Bryozoa - ZMB. 1 records from Nothrus furcatus. 34 records from Faunal assemblage of sediment core TR149-38b. 2 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 71 records from Nottekanal, Klasse 7 - 10. 84 records from Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China. 106 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 35 records from Nannofossil abundance of Hole 37-333. 5923 records from Australian Coral Ecoregions. 1 records from A new species of Ohilimia Strand, 1911 from New Guinea (Araneae: Salticidae). 4845 records from Inventaire des Mollusques Sphaeriidae de France. 11 records from Waldwiese. 12 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 53 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 50 records from Nannofossil abundance of Hole 24-231. 2829 records from Clare Biological Records Centre Dataset 2004-2007. 235 records from Expédition Karubenthos 2012 : données issues des publications. 11 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 884 records from Sea shells of New South Wales. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 35 records from Diatom assamblage in samples from sediment trap OG5. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 15 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 195 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 102 records from Trimma tevegae and T. caudomaculatum revisited and redescribed (Acanthopterygii, Gobiidae), with descriptions of three new similar species from the western Pacific. 5410 records from Collection ornithologique A. Maës. 31 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 5 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 7 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 89 records from Mammal specimens of Komatsu City Museum. 28 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 55 records from Review of the leafhopper genus Anufrievia Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 2 records from A new species of the genus Paracypria (Crustacea: Ostracoda: Cypridoidea) from the Fiji Islands. 883 records from Report on the Danish Oceanographical expeditions 1908-1910 to the Mediterranean and adjacent seas - PelagicPolychaetes. 20891 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 17 records from Örtzemündung (Stedden). 909 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 4 records from Range table from planktonic foraminifers in ODP Hole 160-966F. 102 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 33892 records from National Stag Beetle Surveys (Great Stag Hunts). 3291911 records from Eremaea. 86296 records from Marine Offshore Seabed Survey data held by JNCC. 124477 records from KUBI Ornithology Collection. 86 records from Données naturalistes de Françoise SERRE-COLLET. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 27114 records from Natural History Museum Rotterdam (NL) - Chordata collection. 65 records from Occurrence of mammalia relicts at site Sütto_6. 55 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3626 records from NIWA Invertebrate Type Collection. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 1 records from Rediscovery of the Endangered frog Phrynopus montium (Shreve, 1938) (Amphibia, Anura, Craugastoridae) in the cloud forest of central Peru. 11 records from ALP-PAGES_2017_12_18. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 258 records from Malawi-Histeridae-Biodiversity-Data. 1993 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 69 records from Schiller Gymnasium Hof 10b. 184 records from Biologische Station im Kreis Wesel. 111 records from Planktic foraminifera abundance of Hole 7-64. 1 records from Collections of Phytoplankton at BGBM. 1440 records from The Apterygota collection (EA) of the Muséum national d'Histoire naturelle (MNHN - Paris). 9 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 10 records from Bachabschnitt der Nette (Osnabrück). 37 records from Pollen profile from Seminary School Basin. 16 records from Microzooplankton abundance and biomass at station TT043_4-1. 1 records from Schistura alboguttata, a new loach species of the family Nemacheilidae (Pisces: Cypriniformes) from the Pearl River basin in Guangxi, South China. 91637 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 358 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 3 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 312 records from BIRDRACE Gätkes Erben. 2 records from A new species of Cryptoperla Needham, 1909 (Plecoptera: Peltoperlidae) from Guangxi of China, based on male, female, and larval stage. 36 records from (Tab. 8) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 79-547B, Mazagan Basin west of Morocco. 111 records from Revision of the Eurybrachidae XIV. The Australian genera Olonia Stål, 1862 and Stalobrachys gen. nov. (Hemiptera: Fulgoromorpha). 46 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 8 records from Revision of the Zethus luzonensis species-group (Hymenoptera: Vespidae: Eumeninae), with description of a new species. 3772 records from Fish (KIWE-PI). 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 1 records from Oribates calcaratus. 115 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 6320 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 540 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 182 records from A taxonomic review of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from India. 1000 records from Axel W. Erikssons African Bird Collection at Vänersborg Museum. 6613 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1882 records from Carabidae of the European North-East of Russia. 103 records from BIRDRACE federleser. 558 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 11 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 310 records from The Fishery Grounds near Alexandria.VII.Decapoda.By Heinrich Balss.(1936).Notes and memoirs No. 15. 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 37 records from Palynological analysis of sediment core GeoB9508-5. 18 records from Occurrence of mammalia relicts at site Stematia. 9989 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 35 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 52 records from Pelvicachromis signatus and Pelvicachromis rubrolabiatu
Keywords: GBIF; biodiversity; species occurrences